Natural belief in persistent selves. (17th November 2021) - Collier, Mark
ABSTRACT: In "Of Personal Identity", Hume attempts to understand why we ordinarily believe in persistent selves. He proposes that this ontological commitment depends on illusions and fictions: the imagination tricks us into supposing that an unchanging core self remains static through the flux and change of experience. Recent work in cognitive science provides a good deal of support for Hume's hypothesis that common beliefs about the self are founded on psychological biases rather than rational insight or evidence. We naturally believe in personal persistence, according to this emerging research, because we are prone to categorize the world in terms of hidden essences and structure our lives in terms of whole life stories.